The cross-sectional area of the erector spinae muscle is an adverse indicator for patient with acute exacerbation of chronic obstructive pulmonary disease - Shan Gong; Yankui Wu; Xin Huang; Nan Di; QiLan Wu; Guoping Hu (Scientific Reports)
Abstract To assess the function of the erector spinae muscle’s cross-sectional area (ESMCSA)as a biomarker for the outcome of AECOPD hospitalized patients. Based on chest CT imaging, ESMCSA were caculated following admission. Cox regression analyses, including univariate and multivariate approaches, were utilized to determine risk factors associated with 1-year mortality and initial hospitalization in patients with AECOPD. Additionally, Poisson regression was implemented to assess the rate of rehospitalization. There were 236 AECOPD patient included in the present study, including 59 and 177 patients in the ESMCSA lower group and normal groups respectively. Seventeen patients died within 1 year after discharged from the hospital, and the 1-year mortality rates were 15.3% and 4.5% for the ESMCSA lower group and normal group. A total of 112 patients suffered from 273 rehospitalizations for AECOPD within 1 year after discharged from hospital. Cox regression analysis showed that ESMCSA were associated with the 1-year first hospitalization for AECOPD. Poisson regression analysis showed that ESMCSA were associated with the rate of rehospitalization for AECOPD (IRR = 0.57, 95% CI 0.45–0.73 for univariate analysis, and IRR = 0.56, 95% CI 0.43-0.72for multivariate analysis). Both univariate (HR = 0.29 95% CI: 0.11–0.75) and multivariate Cox regression analyses (HR = 0.35, 95% CI: 0.12–0.99) showed that ESMCSA was associated with 1-year mortality. Lower ESMCSA was a risk factor of 1-year mortality and 1-year rehospitalization for AECOPD.